The Application of Qarinah Qat'iyyah in Syariah Criminal Convictions: A Comparative Analysis of the Concept and its Realisation in the Syariah Court (Kanun: Jurnal Undang-undang Malaysia, 2025)
Justice is the ultimate goal in adjudication within any court. Achieving justice requires judges to rely on methods of evidence, including the use of qarinah. Historically, qarinah has proven to be essential tool in Islamic civilization. In terms of admissibility, qarinah has played a critical role in resolving disputes in cases related to property, marriage-related issues (munakahat), homicide, and cases under takzir, qisas, and hudud punishments. In Malaysia, the Islamic law of evidence concerning qarinah, as applied in syariah courts, is extensively provided under the Syariah Court Evidence Act (Federal Territories) 1997 [Act 561] and other state enactments. However, the concept of qarinah has not been placed on its proper footing. This is due to these acts and enactments being modelled after English legal principles, which narrow the scope and application of qarinah and underutilise its evidentiary weight as a governing law. This article discusses the strength of the dalalah qarinah in convicting cases, particularly in syariah criminal cases. The study evaluates whether the strength of the dalalah qarinah should be determined beforehand by judges when considering the evidence presented. A qualitative approach was adopted, utilising a literature review to analyse primary and secondary sources such as books written by fiqh scholars, statutes, reported and unreported cases, and academic writings. The findings reveal that the strength of the dalalah qarinah, whether it is qarinah qat‘iyyah, qarinah kaazibah, or qarinah dha‘ifah is crucial and must be determined based on the facts of each case. This approach allows syari’e judges greater flexibility in effectively interpreting the dalalah qarinah.Keywords: Qarinah, Islamic evidence law, strength of dalalah qarinah, qarinah qati’yyah, syariah court, evidence acts and enactmentsFull text: PDF